2019
DOI: 10.1002/bab.1766
|View full text |Cite
|
Sign up to set email alerts
|

Wulingsan (Oryeongsan/Goreisan) ameliorate lipid metabolism of obesity rats via regulation of the plasma metabolic profiling

Abstract: Objectives: Wulingsan has been used to cure disease about disorders related to fluid balance for thousands of years. The clinical practice of modern Chinese medicine has found that Wulingsan has the effect on reducing weight and fat, but its mechanism is not clear. This study investigated its effects on obesity rats and explored the underlying mechanisms by analyzing the plasma metabolic profiling. Methods: The effects of Wulingsan on obesity were evaluated with obesity rats induced by high-fat diet. Ultra hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Additionally, GRS has been found to inhibit AQP4 activity and thus has the potential to reduce brain edema after CSDH and other brain injuries [6,7]. Recent studies have also suggested that GRS induces glucose metabolism and insulin sensitivity in people with type 2 diabetes and decreases body weight and fat mass in obese people [8,9]. Despite the fact that many studies have reported various physiological functions of the GRS formula, the exact mechanism of it working is still not fully understood [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, GRS has been found to inhibit AQP4 activity and thus has the potential to reduce brain edema after CSDH and other brain injuries [6,7]. Recent studies have also suggested that GRS induces glucose metabolism and insulin sensitivity in people with type 2 diabetes and decreases body weight and fat mass in obese people [8,9]. Despite the fact that many studies have reported various physiological functions of the GRS formula, the exact mechanism of it working is still not fully understood [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wulingsan originates from "Treatise on Febrile Diseases", which is a traditional Chinese formula composed of polyporus umbellatus, poria cocos, alisma orientalis, atractylodes macrocephala, and cinnamon twig (11,12). It has been reported that Wulingsan exerts protective and fluid balance effects in disorders such as CHF (13), obesity (14), vomiting and diarrhea (15) and dysuria (16). Wulingsan modified formulas (WMF) are made by adding and subtracting herbs from Wulingsan according to the clinical experience, with Wulingsan being the foundation of WMF.…”
Section: Introductionmentioning
confidence: 99%